Objectivity interrogation of racial scholarship in psychology and management - Torrez, Brittany; Dupree, Cydney H.; Kraus, Michael W. (Scientific reports, 2024)
Scholars of color remain underrepresented in US institutions in academia. In this paper, we will examine one factor that contributes to their continued marginalization in psychology and management: the scientific method’s commitment to traditional notions of objectivity. We argue that objectivity—defined as practices and policies rooted in the heightened value placed on a research process that is ostensibly free from bias—is central to the prominence of primarily White scholarship in psychology and management research and remains central to knowledge production. To investigate this, we employ a mixed-methods approach, integrating qualitative and quantitative data to codify how scholars of color experience objectivity interrogation s, or written and verbal questioning in academic contexts that implicates their scientific rigor. We also identify how scholars of color engage in objectivity armoring , or self-presentational strategies (toning down and stepping up) to contend with these interrogations. Finally, we reveal these toning down processes in language use within publications on racial scholarship. Overall, these studies reveal the unique challenges scholars of color face to legitimize and validate their work on race and racism within predominantly White institutions and disciplines.